Performance Characteristics of the Quantitative Method for Staphylococcus aureus in Food Products corresponds to ISO 16140-3: 2021 - Putri, Fannisa; Surati, Sri; Sitorus, Aditya Anugerah Marusaha; Nagur, Kemala Suardi; Cahyaningsih, Eni; Wilasti, Yulin; Sihotang, Maria Arieni Eka Devina (Badan Pengawas Obat dan Makanan, 2024)
Good food sanitation is one of the main pillars for achieving food security goals. High levels of Staphylococcus aureus in food can indicate poor hygiene and handling practices during food production, processing, or storage. Before testing, the laboratory needs to verify the quantitative method for Staphylococcus aureus to produce valid data to ensure food safety and quality. The Centre of National Quality Laboratory of Drugs and Food, Indonesian Food and Drug Authority (FDA) has never verified the Staphylococcus aureus quantification method based on the latest ISO 16140-3:2021. Following the guidelines established in ISO 16140-3:2021, method verification is accomplished by calculating the Interlaboratory Reproducibility Standard Deviation (SIR) for implementation validation and the eBias value for verifying the method's suitability for assessing specific food items. This research was conducted to confirm the ISO 6888-1:2021 as the designated reference method for quantifying Staphylococcus aureus in food products. The cheese was utilized as the test food item to verify the implementation of the method. At the same time, several products, including condensed milk, margarine, baby porridge, cassava chips, and ready-to-eat sausage, were examined as challenging food types. Every chosen food item was artificially contaminated with Staphylococcus aureus WDCM 00034. The SIR value obtained was 0.04 ≤ 2× 0.11 (the lowest mean of SR value from ISO 6888-1:2021), which indicated that the Centre of National Quality Laboratory of Drugs and Food Indonesian FDA was able to implement the method very well. In addition, the eBias value for all types of food tested was below 0.5log10, which showed that the quantitative method for coagulase-positive Staphylococci (Staphylococcus aureus and other types) could be applied in the Centre of National Quality Laboratory of Drugs and Food laboratory for the extensive scope of food.